Internationalization and India’s New Education Policy - Varghese, N.; Mathews, Eldho (International Higher Education, 2021)
Internationalization of higher education in India seems to be motivated more by efforts to extend its soft power and increase its global role than by market mediation for revenue generation. The New Education Policy 2020 (NEP 2020) encourages foreign education institutions to establish a presence in India and recommends setting up Indian institutions abroad.